'From Zionism to Communism': Emilio Sereni and the Consiglio di Gestione in postwar Italy. Issue 4 (November 2021) - Bonfanti, Andrea
Abstract : This essay demonstrates that it is impossible to appreciate the actions of the Italian communist Emilio Sereni without considering his Zionist background. Anyone who is interested in understanding the complexities of communism in the past century and to avoid simplistic conclusions about this ideology will benefit from the study. The problem at stake is that researchers often approach communism in a monolithic manner, which does not adequately explain the multiform manifestations (practical and theoretical) of that phenomenon. This ought to change and to this extent this essay hopes to contribute to that recent strand of historical research that challenges simplistic views on communism. More specifically, by analysing the Management Councils that Sereni created in postwar Italy, we can see that many of their features in fact derived from, or found their deepest origins in, his previous experience as a committed socialist Zionist. The study, then, also relates Sereni to and looks at the broader experiences of early twentieth-century Zionism and Italian communism in the early postwar years.